Forms of Operative and Service Activities of the Ukraine’s State Border Guard Agencies (Units): Concepts and Legal Regulation (Law and Safety, 2019)
As the objective of this article, the characteristics of the concept and legal regulation of the Ukrainian state border guard agencies’ (units) operative and service activities forms are chosen. Such activity is a type of law enforcement activity. The level of the rule of law compliance of such agencies (units) officials and official persons’ service activities depends on the state of its legal regulation.Based on the analysis of the current Ukrainian legislation and scientific views, the author characterized such forms of operative and service activities as border guard and border control. The author's definition of individual concepts is formulated. In particular, according to the author, Ukraine’s state border guard unit is SBGSU state border guard agency’s structural unit, which is responsible for the state border’s certain section protection. The operative and service activities of such units is one of the forms of its state (official) external activity, which is implemented in the border guard service process and carrying out other measures, in accordance with the law enforcement and other SBGSU credentials, concerning persons and legal entities not subordinate to this unit, which implies the origin of all kinds of social relations. The form of operative and service activities of the respective unit is a system of interrelated measures reflecting the content of law enforcement and other credentials of the State Border Guard Service of Ukraine in a certain direction of its state (official) external activities.The forms of operative and service activities are categorized. It is offered to regulate these concepts at the level of the Law of Ukraine “On the State Border Guard Service of Ukraine” and by-laws.
Keywords: the state border guard; the state border guard units; service activity; operative and service activities; forms of operative and service activities; border guard service